2019
DOI: 10.1101/740555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective enhancement of object representations through multisensory integration

Abstract: 1Objects are the fundamental building blocks of how we create a representation of the external 2 world. One major distinction amongst objects is between those that are animate versus 3 inanimate. Many objects are specified by more than a single sense, yet the nature by which 4 multisensory objects are represented by the brain remains poorly understood. Using 5 representational similarity analysis of human EEG signals, we show enhanced encoding of 6 audiovisual objects when compared to their corresponding visua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…There are a number of ways to address these issues. One is to use decoding methods to abstract the amount of information present in a multisensory signal when compared with unisensory signals (Jung et al 2018;Tovar et al 2020). Here, the added activation will only be beneficial if it carries added unique information from each sensory modality.…”
Section: Limitations Of Neuroimaging Studies and Striving Towards Solutionsmentioning
confidence: 99%
“…There are a number of ways to address these issues. One is to use decoding methods to abstract the amount of information present in a multisensory signal when compared with unisensory signals (Jung et al 2018;Tovar et al 2020). Here, the added activation will only be beneficial if it carries added unique information from each sensory modality.…”
Section: Limitations Of Neuroimaging Studies and Striving Towards Solutionsmentioning
confidence: 99%
“…Compared to semantically incongruent or meaningless (arbitrary) multisensory stimuli, semantically congruent stimuli are more easily identified and remembered (e.g. Laurienti et al 2004; Murray et al, 2004; Doehrmann & Naumer 2008; Chen & Spence, 2010; Matusz et al, 2015a; Tovar et al 2020; reviewed in ten Oever et al 2016; Murray et al, 2016b; Matusz et al 2020) and also, more strongly attended (Matusz et al 2015b, 2019a, 2019b; reviewed in Soto-Faraco et al, 2019; Matusz et al 2019c). For example, Iordanenscu et al (2009) demonstrated that search for naturalistic objects is faster when accompanied by irrelevant albeit congruent sounds.…”
Section: Introductionmentioning
confidence: 99%